Essentials of economics - Schiller, Bradley R., 1943- (New York : McGraw-Hill Irwin ; London : McGraw-Hill [distributor], 2009)
This new text for one-term Survey of Economics courses has a two-fold goal: to focus on essential economic concepts and to make them interesting to students. To meet the first goal, the author carefully pruned the Table of Contents to include only those topics which constitute the core of economic concepts. To meet the second, he called on his proven ability to bring economic policy and theory to life, especially by including real-world applications throughout the book, making students feel that economics is a very real-world concern and motivating them to learn more about the basic economic concepts. Also available: instructor's manual (ISBN 0-07-056296-2); and study guide (ISBN 0-07-056295-4).
The Challenge of Economics -- The U.S. Economy -- Supply and Demand -- Microeconomics -- Consumer Demand -- Supply Decisions -- Competition -- Monopoly -- The Labor Market -- Government Intervention -- Macroeconomics -- The Business Cycle -- Aggregate Supply and Demand -- Fiscal Policy -- Money and Banks -- Monetary Policy -- Economic Growth -- Theory and Reality -- International Trade.
Previous ed.: Boston: McGraw-Hill/Irwin, 2007.
Includes index.
1
Keywords: Economics